Epidemiological Description Of The Spread Of Dengue Fever In The Work Area Of The Sikumana Health Center, Maulafa District, Kupang City Period 2017 - 2021 - Manggo, Apliana Wini (Timorese Journal of Public Health, 2024)
Dengue Hemorrhagic Fever is an infectious disease that is still a health problem throughout the world, including Indonesia. DHF cases in East Nusa Tenggara tend to fluctuate every year and are spread in all districts/cities. The case of DHF in Kupang City is still increasing and spread to all Puskesmas work areas including the Sikumana Health Center which is a Puskesmas that experienced an increase in DHF cases from 2017-2020. The purpose of this study was to describe the epidemiology of the spread of dengue fever by person (age and gender), time and place. The type of research used is descriptive research using secondary data. Based on the results of the study, it can be concluded that the cases of DHF in the working area of the Sikumana Health Center, Maulafa District, Kupang City in 2017-June 2021 amounted to 381 cases. The highest cases were in 2020 totaling 171 cases, in 2019 1 person died, in 2020 4 people. DHF cases based on people from 2017-June 2021 when viewed in terms of age were the highest in children aged 5-14 years as many as 191 people and the highest cases based on gender, namely female sex as many as 199 people. DHF cases based on time from period of January2017-June 2021 peaked the highest in January, then in February-August decreased and increased again in November-December. The highest DHF cases based on location were in Sikumana Village with 127 people. Based on the above research, cases of DHF have increased so that health agencies (Puskesmas) take steps to prevent DHF such as PSN, distribution of abate, and 3 M PLUS actions as well as early countermeasures and social services to continue to improve dengue prevention measures with the aim of reducing cases. DBD in the future.